Five Stage Dynamic Time Warping Algorithm for Speaker Dependent Isolated Word Recognition in Speech - Yadav, Munshi; Aalam, Afshar (International Journal of Computer Sciences and Engineering, 2025)
In speech recognition, a speaker dependent isolated word recognition system is used for small vocabulary in different applications for voice control systems. Dynamic Time Warping (DTW) algorithm is used for pattern matching when two sequences of unequal size are available. When test data and reference data or sequences are available of unequal in nature with time domain then existing DTW algorithm takes time more, while proposed solution will give the efficient algorithm which reduces the computation time without degradation of accuracy and efficiency.